2013
DOI: 10.1534/genetics.112.149120
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length Homeostasis Responds to Changes in Intracellular dNTP Pools

Abstract: Telomeres, the ends of linear eukaryotic chromosomes, shorten due to incomplete DNA replication and nucleolytic degradation. Cells counteract this shortening by employing a specialized reverse transcriptase called telomerase, which uses deoxyribonucleoside triphosphates (dNTPs) to extend telomeres. Intracellular dNTP levels are tightly regulated, and perturbation of these levels is known to affect DNA synthesis. We examined whether altering the levels of the dNTP pools or changing the relative ratios of the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 60 publications
(98 reference statements)
5
53
0
Order By: Relevance
“…Deletion of CRT1 further increases dNTP pools in sml1Δ strains (58). We found that deletion of SML1 in dun1Δ pol3-R696W mutants restored dNTP pools to the levels observed in pol3-R696W strains (Fig.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Deletion of CRT1 further increases dNTP pools in sml1Δ strains (58). We found that deletion of SML1 in dun1Δ pol3-R696W mutants restored dNTP pools to the levels observed in pol3-R696W strains (Fig.…”
Section: Resultssupporting
confidence: 50%
“…Although dun1Δ mutants are not able to expand dNTP pools in response to the pol3-R696W mutation (Fig. 3B), the dNTP levels can be increased in dun1Δ strains by deleting the SML1 gene (58). RNR activity is also modulated by Crt1, a transcriptional repressor that binds to and inhibits transcription from RNR2, RNR3, and RNR4 promoters The data are based on DNA sequence analysis of 189 independent Can R mutants of msh6Δ pol3-R696W strains containing pPOL3.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism underlying the phenotype of the Acardi-Goutières syndrome caused by SAMHD1 mutations is still unknown, but the occasional occurrence of mitochondrial DNA deletions might be linked to dNTP pool abnormalities. The recently reported specific influence of the dGTP pool on telomere length homeostasis (38) further emphasizes the importance of keeping dGTP under control. Recent studies have shown that methylation of the SAMHD1 promoter regulates gene expression in human T cells (39) and that the protein is phosphorylated by the cyclin A2/CDK1 complex in cycling cells (40,41).…”
Section: Discussionmentioning
confidence: 94%
“…As telomere shortening has recently been shown to occur upon dNTP depletion (Gupta et al 2013), it is likely that the short telomeres in CCR4-NOT and 9-1-1 mutants are at least partially due to this mechanism. Consistent with a model for increased replication stress in tel1-D xxx-D cells, depleting nucleotide pools by pretreatment with HU (effectively phenocopying the loss of 9-1-1 or CCR4/ POP2) sensitizes tel1-D cells to MMS in a dose-dependent manner, whereas a wild-type strain is unaffected by the HU pretreatment (Figure 8).…”
Section: A Replication Defect Underlies Sensitivity To Mms In Multiplmentioning
confidence: 99%